(untitled) (Journal of the College of Basic Education, 2022)
Strategies language learning are the best and right way to learn a foreign language and also are considered one of the key and important elements for students of EFL to achieve their goals of mastering the foreign language and its culture, because they are an essential part of the improvement of the language framework which the learner develops. Unfortunately, our student-teachers have no idea or belief to use a certain strategy or a certain method of teaching and linking them to the success of the teaching and learning mission. Keywords: student teacher, language learning strategies, methodology, beliefs, English as a foreign language.